The development of a novel fluorescentmarker phage technology system for the early diagnosis of tuberculosis disease - Van der Merwe, Ruben Gerhard (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.